Neuroimaging genetics studies of specific reading disability and developmental language disorder: A review - Landi, Nicole (Lang Linguist Compass, 2019)
Developmental disorders of spoken and written language are heterogeneous in nature with impairments observed across various linguistic, cognitive, and sensorimotor domains. These disorders are also associated with characteristic patterns of atypical neural structure and function that are observable early in development, often before formal schooling begins. Established patterns of heritability point toward genetic contributions, and molecular genetics approaches have identified genes that play a role in these disorders. Still, identified genes account for only a limited portion of phenotypic variance in complex developmental disorders, described as the problem of “missing heritability.” The characterization of intermediate phenotypes at the neural level may fill gaps in our understanding of heritability patterns in complex disorders, and the emerging field of neuroimaging genetics offers a promising approach to accomplish this goal. The neuroimaging genetics approach is gaining prevalence in language- and reading-related research as it is well-suited to incorporate behavior, genetics, and neurobiology into coherent etiological models of complex developmental disorders. Here, we review research applying the neuroimaging genetics approach to the study of specific reading disability (SRD) and developmental language disorder (DLD), much of which links genes with known neurodevelopmental function to functional and structural abnormalities in the brain.